ДЕЯКІ ПИТАННЯ ОРГАНІЗАЦІЇ ПОДАТКОВОГО КОНТРОЛЮ У КРАЇНАХ СВІТУ - Solovyova, Y.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article studies the experience of the USA, Germany and Japan in creation and functioning of the bodies which realize a tax control in these countries, and the possibility of its using in Ukraine as well.